2022
DOI: 10.1186/s43045-022-00238-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression among Palestinian university students: a cross-sectional study during COVID-19 pandemic

Abstract: Background Anxiety and depression are more common among university students than in the general population. It is reported internationally that the COVID-19 pandemic increased the prevalence of anxiety and depression among students. This study aimed to measure the prevalence of anxiety and depression among university students in Palestine and to explore the association between anxiety and depression during the COVID-19 pandemic. A cross-sectional questionnaire-based descriptive study was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Various international studies have reported an increase in mental health disorders among university students who, due to the pandemic, experience high levels of anxiety and depression ( 57 , 58 ), suicidal ideation ( 59 , 60 ), stress, fear ( 61 ), emotional, learning, financial, social, and technological impacts ( 62 ), changes in eating habits, sleep, lifestyle, and behavior ( 63 ), and nightmares ( 64 ). These factors impair academic performance ( 65 ).…”
Section: Post-covid-19 Pandemic: Diagnosis Of Mental Health In Chilea...mentioning
confidence: 99%
“…Various international studies have reported an increase in mental health disorders among university students who, due to the pandemic, experience high levels of anxiety and depression ( 57 , 58 ), suicidal ideation ( 59 , 60 ), stress, fear ( 61 ), emotional, learning, financial, social, and technological impacts ( 62 ), changes in eating habits, sleep, lifestyle, and behavior ( 63 ), and nightmares ( 64 ). These factors impair academic performance ( 65 ).…”
Section: Post-covid-19 Pandemic: Diagnosis Of Mental Health In Chilea...mentioning
confidence: 99%
“…Among the factors that many students going through, including anxiety as they are trying to t in, getting good grades, uncertainty of the future, and being homesick make them more prone to the condition. [2][3][4][5][6] Several literature review and meta-analysis conducted globally revealed that depression is a common occurrence among university students. In a systematic review and meta-analysis conducted in Iran between 1995-2012, 35 published researches which included 9743 study participants have been reviewed; the ndings revealed that the prevalence of depression among university students have been found to be 33%.…”
Section: Introductionmentioning
confidence: 99%